On the notion of retractable modules' in the context of algebras. - Christian Lomp (2014)
This is a survey on the usage of the module theoretic notion of a "retractablemodule" in the study of algebras with actions. We explain how classical results can be interpreted using module theory and end the paper with some open questions.